Skenario Pengembangan Fasilitas Sistem Pengolahan Sampah Dengan Pendekatan Cost Benefit Analysis Di Kelurahan Kedamaian Kota Bandar Lampung - Arlina Phelia; Ria Oktaviani Sinia (Jurnal Serambi Engineering, 2021)
Bandar Lampung City is part of the major city of Lampung province. The problem that arises in Bandar Lampung City is solid waste management. The amount of solid waste in Bandar Lampung City reaches 1000 tons/day. One of the district  of Bandar Lampung named Kedamaian district still uses the old method (collecting-transport-throw) in solid waste management, which  causes the load of waste to accumulate in the landfill. The constraints encountered  this time are the absence of sorting locations  and limited land. Kedamaian district needs to develop waste  treatment facilities, an approach based on  Cost Benefit Analysis (CBA). The results show  from the analysis that BCR in the scenario A 1 is 0.85 with NPV - Rp. 72.968.828. the  activity in the existing conditions can still be carried out, but the waste reduction has not been maximized to the TPS (Container). Scenario B, NPV is Rp. 95.319.338 and BCR is 1.13, which value of BCR is 1. This indicates that a waste processing facility  in the Kedamaian District is suitable to  operate  with TPS-3R. The results of scenario B are  obtained by increasing the effectiveness of processing facilities to 100% by  2025. In 2025, with the implementation of the TPS-3R obtained, BCR is 1.20 with NPV is Rp. 218.447.621.